Insulinoma Unmasked: A Continuous Glucose Monitoring-Fueled Journey - Andrijana Koceva; Mitja Krajnc (Current Oncology)
Insulinomas are rare functional neuroendocrine tumors that are usually indolent and small. Due to their rarity, there is often a delay in disease recognition and diagnosis, and small tumor size makes their localization challenging. Glucose monitoring and dietary modification with or without pharmacotherapy are crucial during diagnostics, and surgery is the only definite treatment. Continuous glucose monitoring (CGM) systems can be a valuable tool in managing insulinoma patients. We present three patients with confirmed endogenous hyperinsulinemic hypoglycemia undergoing tumor localization, medical treatment, and surgery while wearing a CGM system. By accurately depicting glucose fluctuations, CGM can help prevent hypoglycemia, decrease hypoglycemia unawareness, track hypoglycemia frequency, aid in medical therapy dose titration, and confirm a cure after surgery.